Factibilidad para la creación de un departamento de atención integral de los y las adolescentes, en el centro de salud “Hospital El Empalme”, año 2012 - Delgado Carreño, Mónica Lourdes (2012)
This research was conducted in El Empalme city, to 167 km from the city of Guayaquil, located northeast of the province of Guayas, its limits are: in the west Guayas, on the north Manabí and south by Los Ríos; minimum temperature is 21 ° C, an average annual precipitation 1600-3200 mm and its climate is tropical. The study was executed in 180 days. This work began with the formulation of the problem to investigate, which was based on assessing disorientation in interpersonal relationships and performance in society that creates the lack of a comprehensive service department for adolescents in the health center "El Empalme Hospital ". The proposed objectives for the project were diagnosed by a market study the need for the creation of the department of comprehensive care for adolescents in the Health Center "El Empalme Hospital", to develop a technical and economic study should determine the investment needed for the project and determine the financial feasibility of this study for the creation of the department of comprehensive care for adolescents in the Health Center "El Empalme Hospital", in 2012. In order to comply with the objectives of this work, it was necessary to use the methods: inductive, deductive, and scientific research. The types of research: the field because it made the scene, literature because we rely on statistical studies, books and tax provisions, and as applied through interviews, surveys and observations, we aimed to do, to act, builds and modify until the printing of the final work. The survey was conducted by taking a sample of 371 adolescents ranging in age from 10 to 19 years, in the urban area of the El Empalme city. Research deepened in the feasibility study and market analysis components, technical and financial, information that became the basis of support for the financial evaluation. The profitability analysis was gotten by the following formulas: Total costs, asset depreciation, accumulated depreciation, cash flow breakeven (PE), Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (R. B / C). To culminate the research could be analyzed in El Empalme city, there is only a program of care for adolescents (National Council for Children and Adolescents); logging into your database 10 teen visits a week; estimating attention annual 480 teenagers and children served. With the flow of care that currently owns the National Council of childhood and adolescence, not even reach 1% of the current demand for care services which require differentiated adolescents at El Empalme city. Thus, the project aims to meet 1440 adolescents in different service areas by 2012, maintaining a growth rate of 2% for the following years, thus serving to 2.58% of future demand in the first year of the project, and grow gradually to 3.42% in 2016. The technical study found that the total required investment and operations amounted to ($ 149,239.60), which as it is a public entity, will be analyzed through the Ministry of Public Health for the allocation of funds. The economic and financial evaluation, determined that the creation and implementation of comprehensive care department adolescents results in obtaining several benefits will be achieved in the social development of adolescents in society and create sources work, and above all profitable, with an NPV of 820,170.12, the current cost benefit is $ 2,33 and the internal rate of return of 182.75% obtained is very much higher than the financial cost. Finally we concluded that the hypothesis is fulfilled since the feasibility study determined that if there is profitability in the implementation of the department of comprehensive care for adolescents in the health center "El Empalme Hospital".